Chrystocentryzm w teorii i praktyce przepowiadania słowa Bożego - Szewczyk, Leszek (Studia Pastoralne, 2026)
Christocentrism is a viewpoint or an attitude according to which Jesus Christ is the central point of the whole reality of the thoughtful world and most of all a man. The need to apply christocentrism in the preaching ministry is underlined by the teaching of the Church, especially after Vaticanum II. Also a contemporary homiletics theory states that the whole preaching should be christocentric since God revealed himself in the fullest way in Jesus Christ and it is in Him where the salvation of the world and man takes place. The question is, however, whether the practice follows the guidelines? The aim of this study is an attempt to answer the following question: to what extent contemporary preachers apply the rule of christocentricism and in what way it is manifested in their practice? From the conducted analyses it can be seen that chrystology-oriented issues are common ones in preaching. Priests talk about issues of divinity and humanity of Christ very often. The same applies to mysteries of His life and actions within the Church. In most cases they are faithful to the Church’s guidelines to place Christ in the centre of each preaching. This positive assessment of the contemporary preaching requires, however, a few words of comment concerning certain deficiencies. The most common mistakes in christocentric preaching are as follows: historicism, inadequate proportions between a redemptive indicative and a moral imperative as well as a disturbed rules of a hierarchy of the articles of faith in preaching.